(untitled) (Nepal Journal of Health Sciences, 2022)
Introduction: Self-esteem is related to self-worth which fuels motivation, productivity, and efficacy which is considered of high value in academic performance. However, no such studies have been published in Nepal. Objective: We aimed to investigate the association between self-esteem and academic performance of medical undergraduates in Western Nepal. Results: This analytical cross-sectional study was carried out among 226 undergraduate medical students. The majority of the participants had high self-esteem with a median self-esteem score of 29. The female participants had higher scores as well as academic performance than males. We found no association between self-esteem and academic performance. Conclusions: We found no significant relationship between self-esteem and the academic performance of medical undergraduates.